Bioinspired Microtexturing for Enhanced Sweat Adhesion in Ion-Selective Membranes - Marc Josep Montagut Marques; Takayuki Masuji; Mohamed Adel; Ahmed M. R. Fath El-Bab; Kayo Hirose; Kanji Uchida; Hisashi Sugime; Shinjiro Umezu (Cyborg and Bionic Systems)
Advancements in health wearable technology hold the potential to prevent critical health issues such as hyponatremia and other hydration-related conditions often triggered by intense physical activities. Approaches to address this issue include the development of thin-film wearable sensors incorporating carbon nanotubes (CNTs), which offer scalability, lightweight design, and exceptional electrical properties. CNT paper serves as an ideal substrate for electrochemical sensors like ion-selective membranes (ISMs), enabling effective on-skin electrolyte monitoring. However, current on-skin devices often face limitations in maintaining performance during human motion. This study introduces a bioinspired surface texturing technique that mimics the microstructures of rose petals to enhance wettability, self-cleaning, and ISM sensitivity. By replicating the mechanical properties of the surface texture found on rose petals, the newly developed ISM achieves accurate measurements across a 2-mm air gap, offering an improved interfacing solution that promotes better sweat recirculation and comfort. This advancement overcomes the constraints of traditional sensors, paving the way for more reliable and effective noninvasive health monitoring in real-world conditions.